Changing attitudes toward redistribution: The role of perceived economic inequality in everyday life and intolerance of inequality - García Castro, Juan Diego (2021)
Modern societies are characterized by economic inequality. Redistributive policies are one of the means to reduce it. We argue that perceived economic inequality in everyday life and intolerance of it are central factors to enhance positive attitudes toward redistribution. To test it, we conducted a four-wave longitudinal panel study in Chile with a sample of 1221 college students (at T1 – baseline, 960 at T2, 926 at T3, and 787 at T4; Mage = 18.89). As expected, a cross-lagged longitudinal analysis controlled by household income confirmed a positive relationship between perceived economic inequality in everyday life and intolerance of inequality, which in turn was positively associated with support for redistributive policies. These results were stable and consistent over time, supporting the idea that perceived economic inequality in everyday life enhances positive attitudes toward redistribution by increasing intolerance of it. Results highlight the important role played by perceived inequality in everyday life.